Liberation From Renal Replacement Therapy After Cadaveric Liver Transplantation. Issue 11 (November 2016) - Hilmi, Ibtesam A.; Al-Khafaji, Ali; Damian, Daniela; Rosario-Rivera, Bedda L.; Abdullah, Ali; Kellum, John A.
Abstract : Background: Renal failure requiring renal replacement therapy (RRT) is common in patients with end-stage liver disease (ESLD) and is associated with worse outcomes following liver transplantation (LT). We investigated the factors associated with liberation from posttransplant RRT and studied the impact of RRT on patient and graft outcomes. Methods: A 5-year retrospective study of ESLD patients who received pretransplant RRT was conducted. Variables associated with liberation from RRT at 30 days and at 1-year posttransplant were analyzed. We used propensity matching to compare patient and graft outcomes in the study cohort to those of a control group who underwent LT but not pretransplant RRT. Results: Sixty-four patients were included in the study. Twenty-four (38%) were liberated from RRT at 30 days posttransplant. Duration of pretransplant RRT (odds ratio [OR], 0.94; 95% confidence interval [CI], 0.89-0.98) and severe postreperfusion syndrome (OR, 0.26; 95% CI, 0.08-0.87) were significantly associated with continued RRT at 1-month posttransplant. At one year, 34 (53%) patients were liberated from RRT. Age was significantly associated with lack of liberation from RRT (OR, 0.933; 95% CI, 0.875-0.995). Compared with propensity matched controls, patients who received RRT pretransplant had worse graft and patient survival at 1 year (52% vs 82%; P = 0.01, and 53% vs 83%; P = 0.003, respectively). Conclusions: In ESLD patients who received pretransplant RRT, one third were liberated from RRT at 1 month, and half at 1 year. Longer duration of pretransplant RRT, postreperfusion syndrome, and older age were associated with lower likelihood of liberation from RRT. Patients who required pretransplant RRT had worse graft and patient survivals compared to matched patients who did not require RRT. Patients who were liberated from RRT post-LT had similar outcomes to patients who never required pre-LT RRT.